Pulsatility of the umbilical cord in full-term natural childbirths - Thamires Ribeiro Marques Mendonça; Regina Célia Sales Santos; Pollyana Campos Lima; Maria Gabriella Silva Araujo; Maria Elisângela Torres Lima Sanches; Jovânia Marques Lima e Silva (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective Measure umbilical cord pulsatility time and evaluate correlation/association with maternal and neonatal characteristics. Method Cross-sectional study, with 76 binomials, carried out in 2017, in a maternity hospital in Alagoas. Analysis with Pearson or Spearman correlation test and Mann-Whitney or Kruskal-Wallis test. Results Sixty-two parturients and their newborns participated of the research. The women had a gestational age ≥ 37 weeks, natural cephalic birth, without distortions. The newborns had average weight of 3326.29g, mostly male. The umbilical cord pulsatility time was 285.48s. There is a correlation between umbilical cord pulsatility time and placental delivery time (p<0.001). Other correlations/associations were not significant. Conclusion It suggested using a correlation between pulsatility time and placental delivery time in clinical decision making for good practices in childbirth assistance.